Evaluation of the Effectiveness of Digital Training Program for Farmers in Increasing the Adoption of Modern Agricultural - Maula, Indi Millatul (Politeknik Siber Cerdika Internasional, 2025)
Digital transformation in the agricultural sector is an important agenda in increasing the productivity and efficiency of farming, especially in the era of the Industrial Revolution 4.0. This study aims to evaluate the effectiveness of digital training programs organized for farmers in increasing the adoption of modern agricultural technology. The method used is a qualitative approach with a case study design. Data were collected through in-depth interviews, direct observations, and distributing questionnaires to 20 farmers who participated in the digital training program in Banyumas Regency, Central Java. The results showed that digital training had a positive impact on improving digital literacy, confidence, and technology adoption behaviors, such as the use of weather applications, digital record keeping, and online farm marketing platforms. Findings also showed that technology adoption tended to be higher among farmers who received post-training assistance. However, challenges such as device limitations, networks, and technological complexity remain as barriers. This research suggests that digital training programs should be designed in a contextual and sustainable manner so that digital agricultural transformation can be implemented effectively and inclusively.